STRATOSPHERIC AND MESOSPHERIC CARBON-MONOXIDE - FIRST RESULTS FROM THE VALIDATION OF THE ISAMS MEASUREMENTS AT 4.6-MU-M - Lopezvalverde, M; Lopezpuertas, M; Marks, C; Taylor, F; Kerridge, B; Remedios, J; Dudhia, A; Rodgers, C (1994)
Limb sounding measurements of the atmospheric emission at 4.6 μm by the Improved Stratospheric and Mesospheric Sounder (ISAMS) on board the Upper Atmospheric Research Satellite (UARS) are used to retrieve CO abundance in the middle atmosphere. In this paper we focus on the main problems related to the validation of these measurements and to their interpretation. We also present preliminary results of radiance fields and CO concentrations in the middle atmosphere with a brief discussion of their most relevant features. © 1994.